Circulating levels of monocyte chemoattractant protein‐1 as a potential measure of biological age in mice and frailty in humans. Issue 2 (31st December 2017) - Yousefzadeh, Matthew J.; Schafer, Marissa J.; Noren Hooten, Nicole; Atkinson, Elizabeth J.; Evans, Michele K.; Baker, Darren J.; Quarles, Ellen K.; Robbins, Paul D.; Ladiges, Warren C.; LeBrasseur, Nathan K.; Niedernhofer, Laura J.
Summary: A serum biomarker of biological versus chronological age would have significant impact on clinical care. It could be used to identify individuals at risk of early‐onset frailty or the multimorbidities associated with old age. It may also serve as a surrogate endpoint in clinical trials targeting mechanisms of aging. Here, we identified MCP‐1/CCL2, a chemokine responsible for recruiting monocytes, as a potential biomarker of biological age. Circulating monocyte chemoattractant protein‐1 (MCP‐1) levels increased in an age‐dependent manner in wild‐type (WT) mice. That age‐dependent increase was accelerated in Ercc1 −/Δ and Bubr1 H/H mouse models of progeria. Genetic and pharmacologic interventions that slow aging of Ercc1 −/Δ and WT mice lowered serum MCP‐1 levels significantly. Finally, in elderly humans with aortic stenosis, MCP‐1 levels were significantly higher in frail individuals compared to nonfrail. These data support the conclusion that MCP‐1 can be used as a measure of mammalian biological age that is responsive to interventions that extend healthy aging.